A comparative study of pregnancy complications and outcomes for the years 1999 and 2004 at a rural hospital in South Africa: Implications for antenatal care - Monjurul Hoque; Shahnaz Hoque (AOSIS, 2010)
Background: Detection and management of high-risk pregnancies, all the way through antenatal care, have been advocated as a high-quality mean of reducing maternal and perinatal morbidity and mortality. Objectives: This study reviewed the demographic variables, pregnancy and obstetric complications and perinatal outcomes for the years 1999 and 2004 in a rural hospital in KwaZulu-Natal Province, South Africa, with the aim of evaluating trends and gaps that may enhance appropriate strategies for improvement of antenatal care. Method: A retrospective comparative study, with representative samples of pregnant women, were randomly selected for the respective years 1999 and 2004. Descriptive statistics were calculated depending on measurement scale. A Z-test was carried out to assess the significant difference (p < 0.05) in proportions between pregnancy complications and outcomes of the groups. Multivariate logistic regression analysis was undertaken to determine the significant predictors for outcome variables. Results: The numbers of pregnancies among young women (< 25 years) increased significantly by 8% (p < 0.05) in the year 2004. Compared with 1999, the reduction in the numbers of pregnancies (1%) among higher parity (parity 5 or more) women in 2004 was remarkable. There were significant reductions of eclampsia, anaemia and post partum haemorrhage. Women with breech presentation were 3.75 times more likely to deliver preterm, and 5.45 times more likely to deliver low birth-weight babies. Similarly, women with pregnancy-induced hypertension were more likely to have preterm (OR = 3.50, 95% CI 2.83; 4.35) and low birth-weight babies (OR = 2.09, 95% CI 1.62; 2.71). Eclampsia was also a risk factor associated with preterm deliveries (OR = 6.14, 95% CI 3.74; 10.09) and low birth-weight babies (OR = 3.40, 95% CI 1.83; 6.28). Conclusion: This study suggests that further research is needed to find the causes of higher rate of teenage pregnancies and an increase in quality of antenatal care is more important in improving maternal and perinatal health. Training of staff to standard protocol and guidelines on antenatal care and care during delivery, and adherence to it, should be encouraged to improve maternal and child health in South Africa.